Global Commodity Chains and Kerala Report on a Seminar - M K SUKUMARAN NAIR (Economic and Political Weekly November 8, 2003, 2003)
An international seminar on `Agro-Industrial Global Commodity Chains: Implications for Business Strategies and Policies for Kerala' in Kochi in September sought to understand the emerging patterns of social and economic organisation of production in the context of rapid internationalisation. In relation to Kerala it was recognised that there was much scope for upgrading agro processing activities with a view to enhancing productivity and competitiveness in the stagnating commodity producing sectors.